Measures of Functional Status in Community-Dwelling Elders - Sherman, Scott E. (Blackwell Science Inc, 1998)
OBJECTIVE: To evaluate two performance-based measures of functional status and assess their correlation with self-report measures. DESIGN: Cross-sectional study. PARTICIPANTS: Of the 363 community-dwelling elders enrolled in a trial of comprehensive geriatric assessment who participated, all had at least one of four target conditions (urinary incontinence, depression, impaired functional status, or history of falling). MEASUREMENTS: Two performance-based measures, National Institute on Aging (NIA) Battery, and Physical Performance Test (PPT), and three self-report functional status measures, basic and intermediate activities of daily living and the Short-Form-36 (SF–36) physical functioning subscale, were used. Measures of restricted activity days, patient satisfaction and perceived efficacy were also used. MAIN RESULTS: All measures were internally consistent. There was a high correlation between the NIA and PPT (κ = 0.71), while correlations between the performance-based and self-report measures ranged from 0.37 to 0.50. When patients with values above the median on the two performance-based measures were compared with those below, there were significant differences (p≤ .0001) for age, number of medications, and the physical function, pain, general health, and physical role function SF-36 subscales. CONCLUSIONS: Performance-based measures correlated highly with each other and moderately with questionnaire-based measures. Performance-based measures also had construct validity and did not suffer from floor or ceiling effects.